Feelings and Finance, as Based on Two Literary Works - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
In this article a French bank of 1850s in Paris is compared with an American one in an unknown state in the United States of America in 1970s. The French bank depicted by Zola for Paris and the American bank thought up by Arthur Hailey are, despite the time and geography differences, very similar in their functions. The former is only more deeply embedded in the stock exchange while the latter is essentially dependent upon loans made possible thanks to depositors. A war of nerves and extreme stress underline the themes of both of those superb novels. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Bank; money; stock exchange; shares; feelings